Aetna Sewing Machine, E.G. Morrison, Plasterer; James I. Wingate, Painter; Snaderson Bros. & Co. - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Aetna Sewing Machine, E.G. Morrison, Plasterer; James I. Wingate, Painter; Snaderson Bros. & Co. from the 1870 Boston City Directory